Société, politique et religion en Gaule avant la Conquête - Stéphane Verger (Pallas, 2009)
The information provided by Caesar in his Commentaries, combined with the more and more pertinent data provided by archaeology, allows to elaborate a global picture of the functioning of the Gaulish society before the Conquest, which is liable to be confronted with the present anthropological studies on the modern tribal societies. We can especially perceive the complexity of the segmental system that documents from the VIth century B.C., the determining place of the rival factiones, the superiority of an aristocratic culture of honour which determines the set of the social practices, and finally the paper of religious mediators carried out by the druids in a society dominated by the exacerbation of the rivalries between great characters.